2013
DOI: 10.2522/ptj.20120414
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Back School Versus McKenzie Exercises in Patients With Chronic Nonspecific Low Back Pain: A Randomized Controlled Trial

Abstract: The McKenzie method (a more resource-intensive intervention) was slightly more effective than the Back School method for disability, but not for pain intensity immediately after treatment in participants with chronic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 54 publications
5
119
1
5
Order By: Relevance
“…There are no similar studies investigating the efficacy of McKenzie exercises on MND while there are other studies sharing the same principal but pertaining to a related area (lumber spine). For instance, Garcia et al, (2013) showed concurrence with this study as they reported that McKenzie method was more effective than Back School method for promoting physical function in patients with low back dysfunction [10]. Regarding the neck region, there were studies that demonstrated the efficacy of McKenzie approach on cervical radiculopathy.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…There are no similar studies investigating the efficacy of McKenzie exercises on MND while there are other studies sharing the same principal but pertaining to a related area (lumber spine). For instance, Garcia et al, (2013) showed concurrence with this study as they reported that McKenzie method was more effective than Back School method for promoting physical function in patients with low back dysfunction [10]. Regarding the neck region, there were studies that demonstrated the efficacy of McKenzie approach on cervical radiculopathy.…”
Section: Discussionsupporting
confidence: 64%
“…Stabilization and endurance exercises have been recommended as an effective intervention for patients with neck pain [9]. McKenzie exercises have also been also recommended to reduce spinal pain [10]. Stabilization and McKenzie exercises utilize different protocols to reduce pain and there is controversy about which is more effective in spinal pain [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the frequency of visits due to pain (depending on the severity of pain) does not need to exceed 1-2 times a week. the next visit should begin with the patient demonstrating the self-therapy activities he or she performs at home in order to improve their effectiveness [49,[51][52][53][54].…”
Section: Palpation Assessment For Physiotherapeutic Needsmentioning
confidence: 99%
“…A further problem is that the current literature only offers studies which are not clearly comparable due to their different composition of control groups and the varying length and structure of the programs [15][16][17]. At least the studies of Lamb et al, [18] and O'Sullivan et al, [19] are reproducible regarding study designs and therapy measurements.…”
Section: Introductionmentioning
confidence: 99%